Synthesis, characterization and antibacterial evaluation of novel 2-mercaptobenzothiazole derivatives bearing 2-aminonicotinonitrile moiety - Mahdi, Monther Faisal; Al-Smaism, Rafah Fadhil; Ibrahim, Noor Waleed (European Journal of Chemistry, 2016)
An efficient methods has been described for the synthesis of new 2-aminonicotinonitrile derivatives (6a-f) bearing benzothiazole nucleus by solvent free microwave or ultrasound irradiation. The reaction proceeds via one-pot four-component by cyclo condensation reaction of heterocyclic methyl ketones (4a), malononitrile, ammonium acetate and aryl aldehydes. Chalcones intermediate and final compounds were also synthesized by conventional methods, the result confirms that microwave method showed higher yield and purity than conventional one. The synthesized compounds were characterized by FT-IR spectroscopy and 1H NMR. Antibacterial activities of the synthesized compounds have been tested against four different types of bacteria; most of the tested compounds showed significant biological activities.